Outcomes and Predictors of Ventriculoperitoneal Shunt Failure in Children with Hydrocephalus - Hossain, Md Delwar; K M N, Ferdous; A, Rahman (Journal of Paediatric Surgeons of Bangladesh, 2025)
Background: Pediatric hydrocephalus is a common neurological condition requiring surgical intervention, primarily through ventriculoperitoneal (VP) shunt placement. Despite widespread use, VP shunt systems face complications, with failure rates remaining high, particularly in low- and middle-income countries (LMICs). Identifying risk factors for shunt failure is critical for improving outcomes. This study aimed to determine the incidence, types, timing, and predictors of VP shunt failure in children with hydrocephalus at a tertiary pediatric neurosurgical center in Bangladesh. Methods: This prospective observational study was conducted in the Department of Pediatric Neurosurgery, Bangladesh Shishu Hospital and Institute, from July 2021 to June 2024. A total of 226 pediatric patients (aged 0–18 years) who underwent primary or revision VP shunt procedures were included in this study. Baseline demographic and clinical data were collected. Patients were followed for one year postoperatively to assess shunt failure incidence and timing. Statistical analy ses included chi-square and t-tests to identify risk factors associated with failure. Results: The overall shunt failure rate was 32.7%, predominantly due to mechanical obstruction (20.4%) and infection (10.2%). Most failures occurred within six months post-surgery (75.7%). Significant predictors of failure were age under six months (p=0.004), emergency surgery (p=0.024), post-infectious hydrocephalus (p=0.001), and longer surgery duration (p<0.001). Conclusion: VP shunt failure in pediatric hydrocephalus is influenced by patient age, surgical urgency, etiology, and operative factors. Tailored surgical strategies and stringent perioperative care are essential to improve outcomes in this vulnerable population. Journal of Paediatric Surgeons of Bangladesh (2021) Vol. 12 (1 & 2): 30-36